Pole tilt monitoring system using MEMs accelerometer and BeagleBone Black - Lok De Yong; Nurul Asyikin Mohamed Radzi; Yanti Erana Jalil (Institute of Advanced Engineering and Science, 2018)
Electric pole could tilt in the event of heavy storms, soil erosion and object crashing onto poles, causing serious damages if they are not fixed before condition worsen. Therefore, to monitor the health of the electric pole, a system to monitor its tilting angle is needed. In this paper, for the first time, to the best of our knowledge, an integration of Micro Electro-Mechanical Systems (MEMs) accelerometer with BeagleBone Black microcomputer will be used to develop an electric pole tile angle monitoring system. The accuracy of measuring tilt angle using single axis accelerometer versus triple axis accelerometer and the effect of rolling on tilt angle reading using single axis accelerometer versus triple axis accelerometer will be presented. Three-axis accelerometer achieves greater accuracy as the percentage error of tilting and rolling for the three-axis accelerometer are better than the single-axis accelerometer.